2008
DOI: 10.1016/j.exger.2007.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondrial DNA mutations in aging and sarcopenia: Implications for the mitochondrial vicious cycle theory of aging

Abstract: Aging is associated with a progressive loss of skeletal muscle mass and strength and the mechanisms mediating these effects likely involve mitochondrial DNA (mtDNA) mutations, mitochondrial dysfunction and the activation of mitochondrial-mediated apoptosis. Because the mitochondrial genome is densely packed and close to the main generator of reactive oxygen species (ROS) in the cell, the electron transport chain (ETC), an important role for mtDNA mutations in aging has been proposed. Point mutations and deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
154
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(162 citation statements)
references
References 62 publications
6
154
0
2
Order By: Relevance
“…Although the generation of ROS depends on the specific defect in OXPHOS components and residual activities, the random nature of mutations in these mice would be expected to create such defects. The lack of oxidative stress raises questions of whether naturally accumulating mtDNA mutations are responsible for increased oxidative damage [15]. These results imply that mtDNA mutations could accelerate aging, even without the involvement of oxidative stress.…”
Section: Contribution Of Mutated Mitochondrial Dna To Aging and Oxidamentioning
confidence: 86%
“…Although the generation of ROS depends on the specific defect in OXPHOS components and residual activities, the random nature of mutations in these mice would be expected to create such defects. The lack of oxidative stress raises questions of whether naturally accumulating mtDNA mutations are responsible for increased oxidative damage [15]. These results imply that mtDNA mutations could accelerate aging, even without the involvement of oxidative stress.…”
Section: Contribution Of Mutated Mitochondrial Dna To Aging and Oxidamentioning
confidence: 86%
“…Reactive oxygen species (ROS) additionally play a key role in triggering sarcopenia in skeletal muscle during age progression (Hiona and Leeuwenburgh, 2008 ). Cells are exposed to oxidative stress as a result of one or more of three factors: i) increase in oxidant generation, ii) decrease in antioxidant protection, and iii) failure to repair oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…These pathological states share unique features and are all characterized by a loss of collagen type I, dysregulated fibroblast-matrix interactions and impaired fibroblast interactions with organ parenchyma, mainly with organ-specific epithelial cells and muscle (Wenk et al, 1999(Wenk et al, , 2004Krtolica & Campisi, 2002;Campisi, 2005;Labat-Robert & Robert, 2007;Treiber et al, 2009). A variety of genetic and environmental factors including increased concentration of ROS, mitochondrial dysfunction (Hiona & Leeuwenburgh, 2008), changes in autocrine, paracrine and endocrine release of hormones, growth factors (Perrini et al, 2010) and cytokines (Coppe et al, 2008) have been identified to contribute to skin aging, sarcopenia and osteoporosis in humans and rodents (Zofkova, 2003;Raisz, 2005;Ralston & de Crombrugghe, 2006;Hiona & Leeuwenburgh, 2008;Marzetti et al, 2009). Research on the regulation of connective tissue organization by enhanced release of ROS from mitochondria during fibroblast aging is a matter of increasing interest and relevance as it may provide ultimate clues for mechanisms underlying disruption of connective tissue homoeostasis in aging-related skin atrophy, sarcopenia and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…With aging, a progressive loss of skeletal muscle mass and strength occurs, a condition termed sarcopenia or muscle atrophy. Similar to skin atrophy and the loss of bone mass in the elderly (osteoporosis), muscle atrophy is a universal characteristic of the aging process in several species from worm to human (Fisher, 2004;Hiona & Leeuwenburgh, 2008). In older individuals, loss of muscle and bone mass is highly predictive of falls (Newton-John & Morgan, 1970;Szulc et al, 2005), disability (Rantanen et al, 1999) and mortality (Metter et al, 2002).…”
Section: Introductionmentioning
confidence: 99%